Prolanis Influence on Decreasing Blood Pressure of Hypertension Patients in Puskesmas Pandak II Bantul 2017 - Florentina Sita Murti; Hari Kusnanto Josef; Wahyudi Istiono (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2019)
Background: People with hypertension over age 25 years reached 40% in 2008 according to the World Health Organization and 75% occurred in developing countries. Hypertension management must be focused on first-rate health care which could reduce death-risk, disabilities, and the cost burden. Badan Pengelola Jaminan Social obliges every first-rate health care to have to apply Program Pengelolaan Penyakit Kronis (Prolanis).Objectives: This study aims to determine the difference of decreased blood pressure in Prolanis and Non-Prolanis groups in Puskesmas Pandak II.Methods: This quantitative research with cohort retrospective design used secondary data of hypertension patients who are following Prolanis compared with those who are not in Puskesmas Pandak II. Data covered characteristics of patients, blood pressure, and Body-Mass Index (BMI) over one year. The analysis used repeated measures ANOVA. Results: The comparison with the treatment group showed significant differences in blood pressure variable, diastolic pressure variable, and BMI, interaction and measureable differences during the study period in all three variables. There was an uptrend in the Non-Prolanis group and a downtrend in the Prolanis group.Conclusions: Decreased blood pressure of patients with hypertension is better in Prolanis than Non-Prolanis groups.